Radiation recall pneumonitis induced by erlotinib after palliative thoracic radiotherapy for lung cancer: Case report and literature review. Issue 1 (5th February 2016) - Awad, Raef; Nott, Louise
Abstract: Radiation lung injury usually develops 1–6 months after cessation of radiation therapy to the lung. Acute change in the previously irradiated lung after administration of antineoplastic agent is known as radiation recall pneumonitis. Erlotinib is a reversible epidemal growth factor receptor tyrosine kinase inhibitor, which is effective for patients with advanced lung cancer with epidermal growth factor receptor mutations. Here we report a rare case of radiation recall pneumonitis following treatment with erlotinib 4 months after palliative radiotherapy to the lung. A 76‐year‐old man with non–small cell lung cancer was treated with polychemotherapy, palliative thoracic irradiation (30 Gy in 12 fractions) and erlotinib thereafter. Two months after administration of erlotinib he developed of severe dyspnea, cough, anorexia and lack of energy. CT chest revealed extensive radiation pneumonitis. Erlotinib was ceased and high‐dose steroids were started. The symptoms ultimately resolved and erlotinib was resumed cautiously after 11 weeks. On dosimetric analysis, lung V20 and the mean lung dose were 20.33% and 10.7 Gy, respectively, and hence, the risk of radiation pneumonitis is very low. These data indicate that systemic administration of erlotinib after low‐dose palliative radiation therapy can be associated with unexpected toxicity when visceral organs are within the radiation field.